Digital Transformation and Competitive Advantage in the Architectural Creative Economy: A Resource-Based View Perspective - Sulistyowati, Ecclisia; Isa, Muzakar; Fuadah, Rowiyatul (Universitas Muhammadiyah Semarang, 2026)
This study examines how digital transformation reshapes the competitiveness of the creative economy, with particular reference to the architectural subsector, through the lens of the Resource-Based View (RBV). It adopts a qualitative descriptive approach based on a critical literature review of internationally reputable journals, synthesising conceptual developments, empirical findings, and contemporary scholarly debates. The analysis focuses on three interrelated dimensions: (1) the evolution of architectural creative practices and services in the digital era, (2) the emergence of new creative business models, and (3) strategic approaches to strengthening subsectoral competitiveness. The synthesis indicates that digital transformation within the architecture, engineering, and construction (AEC) ecosystem driven by BIM-enabled workflows, cloud-based collaboration, and data-driven services such as digital twins has prompted a shift in value creation away from project-specific deliverables towards more standardised, replicable, and knowledge intensive creative services. From an RBV perspective, technology alone does not generate competitive advantage. Rather, competitiveness arises when firms effectively orchestrate strategic resources such as creativity, professional experience, digital literacy, reputation, and knowledge assets into organisational capabilities. These capabilities include the standardisation of digital processes, quality control systems, contract and risk governance, and intellectual property management. Such capabilities underpin business model innovation, including the productisation of services, data-driven advisory offerings, and mechanisms for recurring value capture. Collectively, these developments enhance differentiation and enable architectural firms to scale and extend their market reach.Keywords: creative economy; architectural subsector; digital transformation; resource-based view; business model innovation.